A hybrid multi-population genetic algorithm applied to solve the multi-level capacitated lot sizing problem with backlogging - Toledo, Claudio Fabiano Motta; De Oliveira, Renato Resende Ribeiro; Morelato França, Paulo [UNESP] (Elsevier, 2013)
The present paper proposes a new hybrid multi-population genetic algorithm (HMPGA) as an approach to solve the multi-level capacitated lot sizing problem with backlogging. This method combines a multi-population based metaheuristic using fix-and-optimize heuristic and mathematical programming techniques. A total of four test sets from the MULTILSB (Multi-Item Lot-Sizing with Backlogging) library are solved and the results are compared with those reached by two other methods recently published. The results have shown that HMPGA had a better performance for most of the test sets solved, specially when longer computing time is given. © 2012 Elsevier Ltd.
Keywords: Backlogging; Fix and optimize; Genetic algorithms; Hybridization; Lot sizing; Multi-level; Heuristic methods; Mathematical programming